2019
DOI: 10.1007/s11910-019-0948-5
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Caffeine by People with Epilepsy: the Myths and the Evidence

Abstract: Purpose of review: Caffeine is the most widely consumed central nervous stimulant. For people with epilepsy, it is often unclear whether drinking coffee carries a risk of triggering seizures. Recent findings: The relationship between caffeine, seizures, epilepsy and anti-seizure drugs is not fully understood. Clinical studies are scarce. In animal models, caffeine can increase seizure susceptibility but can also protect from seizures. Effects seem dose-dependent and, influenced but the duration of intake and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 86 publications
(122 reference statements)
1
11
0
Order By: Relevance
“…Thus far, the role of caffeine in the control of epilepsy is unclear. Studies on animal models suggest that depending on the dose and length of caffeine intake, it may have both positive and negative effects on seizure control [ 45 , 46 ]. Moreover, caffeine may reduce the effectiveness of some anticonvulsant drugs, mainly topiramate [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, the role of caffeine in the control of epilepsy is unclear. Studies on animal models suggest that depending on the dose and length of caffeine intake, it may have both positive and negative effects on seizure control [ 45 , 46 ]. Moreover, caffeine may reduce the effectiveness of some anticonvulsant drugs, mainly topiramate [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, numerous studies have indicated that people with epilepsy are less physically active and less willing to participate in sports activities [ 72 ]. In general, fewer people with epilepsy perform physical activity at the recommended level [ 45 ]. Importantly, other studies have addressed the potentially beneficial role of physical activity in improving the cognitive function of patients with epilepsy [ 73 ] and quality of life [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…So far, the role of caffeine in the control of epilepsy is unclear. Studies on animal models suggest that, depending on the dose and length of caffeine intake, it may have both positive and negative effects on seizure control [44,45]. Moreover, caffeine may reduce the effectiveness of some anticonvulsant drugs, mainly topiramate [46].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, numerous studies indicate that people with epilepsy are less physically active and less willing to participate in sports activities [72]. In general, fewer people with epilepsy show physical activity at the recommended level [44]. Importantly, other studies address the potentially bene cial role of physical activity in improving the cognitive function of patients with epilepsy [73] and quality of life [74].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies did not find a relation between exposure to chronic low-dose caffeine or withdrawal from it and seizures [22]. However, there are studies reporting decrease in the duration of convulsions in animals that received caffeine for several days in comparison to ones that received saline, in addition to studies reporting seizures triggered by a single-high caffeine dose [23]. In adult rats with genetic absence epilepsy, seizure activity decreased after an acute dose of caffeine, while chronic doses had no effect [24].…”
Section: Introductionmentioning
confidence: 99%